PENGARUH PENGGUNAAN VIRGIN COCONUT OIL (VCO) DALAM RANSUM TERHADAP PERFORMANS TERNAK BABI FASE STARTER - Tamawiwy, Alfred; Najoan, M.; Mandey, J S; Sompie, F. N (ZOOTEC, 2016)
ABSTRACT   EFFECT OF UTILIZATION OF VIRGIN COCONUT OIL (VCO) IN THE DIET ON PIG PERFORMANCE. Utilization of fats and oils in pig diets is of great importance due to their high energy value. VCO is obtained by cold press processing of the kernel from the coconut fruit. Utilization of virgin coconut oil (VCO) in the diets on pig performance.  The present study was designed to elaborate the effect of utilization of VCO in the diets on energy and protein digestibility of growing pigs. The experiment was conducted using 20 castrated male pigs aged 1.5 - 2.0 months weighing 12,0±2,0 kg. The data were analyzed according to the linear model procedure for ANOVA appropriate for Randomized Block Design with 5 treatments and 4 replications. Treatments were formulated as follow: R0 = 100% control diet + 0% VCO; R1 = 99.5% control diet + 1.0% VCO; R2 = 98.0% control diet + 2.0% VCO; R3 = 97.0% control diet + 3.0% VCO; and R4 = 96.0% control diet + 4.0% VCO. Parameters measured were: daily feed intake, daily gain, daily water consumption. The results showed that the utilization of VCO up to 4% in the diets had no significant effect (P > 0.05) on daily feed intake, daily gain, daily water consumption of pigs. It can be concluded that the addition of VCO up to 4.0% in the diets has no significant meaning on pig performance.   Key words: Virgin coconut oil (VCO), Performance, Growing pigs